2002
DOI: 10.1021/bi0159837
|View full text |Cite
|
Sign up to set email alerts
|

DNA Gyrase Interaction with Coumarin-Based Inhibitors:  The Role of the Hydroxybenzoate Isopentenyl Moiety and the 5‘-Methyl Group of the Noviose

Abstract: DNA gyrase is a major bacterial protein that is involved in replication and transcription and catalyzes the negative supercoiling of bacterial circular DNA. DNA gyrase is a known target for antibacterial agents since its blocking induces bacterial death. Quinolones, coumarins, and cyclothialidines have been designed to inhibit gyrase. Significant improvements can still be envisioned for a better coumarin-gyrase interaction. In this work, we obtained the crystal costructures of the natural coumarin clorobiocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(187 citation statements)
references
References 25 publications
3
184
0
Order By: Relevance
“…The baseline was measured by injecting the ligand into the protein-free buffer solution. Data were analyzed using the MicroCal Origin software and were fitted with a ''one set of sites'' and led to the determination of affinity constants (K) and enthalpy changes (DH) as previously described [17]. Consequently, the entropy variations (DS) were calculated according to the standard equations.…”
Section: Itcmentioning
confidence: 99%
“…The baseline was measured by injecting the ligand into the protein-free buffer solution. Data were analyzed using the MicroCal Origin software and were fitted with a ''one set of sites'' and led to the determination of affinity constants (K) and enthalpy changes (DH) as previously described [17]. Consequently, the entropy variations (DS) were calculated according to the standard equations.…”
Section: Itcmentioning
confidence: 99%
“…Bacterial DNA gyrase is the target of the aminocoumarin antibiotics (Hooper et al, 1982 ;Maxwell, 1999). X-ray crystallographic examinations (Ali et al, 1993 ;Lewis et al, 1996 ;Maxwell, 1993 ;Tsai et al, 1997 ;Lafitte et al, 2002) have demonstrated that as well as the aminocoumarin moieties and the substituted deoxysugar moieties, the prenylated 4-hydroxybenzoate moieties of clorobiocin and novobiocin are essential for the binding of these compounds to the B subunit of gyrase. The affinity of the aminocoumarin antibiotics for The GenBank accession number for the sequence of cosmid K1F2 is AF329398.…”
Section: Introductionmentioning
confidence: 99%
“…Thiosemicarbazide compounds exhibit various biological activities such as anti-bacterial, anti-fungal and especially antituberculosis . Apart from this, coumarins constitute an important class of compounds found throughout the plant kingdom and are known to have diverse activities such as anti-coagulants (Anderson et al, 2002, Tassies et al, 2002, anti-bacterial (Mitscher, 2002, Laffitte et al, 2002, anti-fungal (Moffett, 1964) and cytotoxicity (Weber et al, 1998) properties. The coumarin moiety and related derivatives are also reported to have importance as vasodilators (Hoult & Payá, 1996), anti-mutagenic agents (Pillai et al, 1999), scavengers of reactive oxygen species (Finn et al, 2004), as well as lipoxygenese and cyclooxygenese inhibitors (Kimura et al, 1985, Hofmanová et al, 1998.…”
Section: Methodsmentioning
confidence: 99%
“…For general background to and applications of the title thiosemicarbazide compound, see: Anderson et al (2002); Chulian et al (2009); Desai et al (1984); Finn et al (2004); Hofmanová et al (1998); Hoult & Payá (1996); Kimura et al (1985); Laffitte et al (2002); Mitscher (2002); Moffett (1964); Pillai et al (1999); Shukla et al (1984); Tassies et al (2002); Weber et al (1998). For the preparation, see: Moamen et al (2009).…”
Section: Related Literaturementioning
confidence: 99%